Análise de três técnicas de controle para emprego de um conversor Boost trifásico em uma estrutura retificadora híbrida com suportabilidade a afundamentos de tensão - Silva, Paulo Ricardo da (2018)
This dissertation presents the analysis, the theoretical development and the comparison of the control methods by: (i) PWM; (ii) Hysteresis; and (iii) dq0, of a three-phase Boost converter when applied to a three-phase hybrid rectifier structure that performs the imposition of sinusoidal input line currents and voltage regulation on the DC bus, both for normal power supply conditions and for conditions Voltages in the AC network. In order to compare the three control methods, the total harmonic distortion indexes of current, power factor and voltage level in the DC bus were analyzed. For computational simulations and mathematical analysis, the software PSim® and Matlab®, respectively, were used. In order to corroborate with the exposed theory and computational simulation analyzes, a prototype of 5 kW based on DSP was constructed and experimental tests carried out in the laboratory allowed to demonstrate that the three control methods, as demonstrated in the computational analysis, ensure sinusoidal currents in line and are able to regulate and maintain the voltage on the constant DC bus.